2017
DOI: 10.1158/1535-7163.mct-16-0465
|View full text |Cite
|
Sign up to set email alerts
|

Biological Role and Therapeutic Targeting of TGF-β3 in Glioblastoma

Abstract: Transforming growth factor (TGF)-β contributes to the malignant phenotype of glioblastoma by promoting invasiveness and angiogenesis and creating an immunosuppressive microenvironment. So far, TGF-β and TGF-β isoforms have been considered to act in a similar fashion without isoform-specific function in glioblastoma. A pathogenic role for TGF-β in glioblastoma has not been defined yet. Here, we studied the expression and functional role of endogenous and exogenous TGF-β in glioblastoma models. mRNA is expressed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Although we did not assess the possibility for TGF-β 3 to be used as a prognostic biomaker or target, analysis of the TCGA data by Seystahl and collaborators revealed that low expression of this isoform was associated with a better prognosis in GBM of the neural subtype whereas it bore no significant effect in proneural, mesenchymal, or classical GBM subtypes. Moreover, their study corroborated that oligonucleotide-based specific inhibition of TGF-β 3 significantly reduced invasiveness in vitro as well as in vivo [ 33 ].…”
Section: Discussionmentioning
confidence: 73%
“…Although we did not assess the possibility for TGF-β 3 to be used as a prognostic biomaker or target, analysis of the TCGA data by Seystahl and collaborators revealed that low expression of this isoform was associated with a better prognosis in GBM of the neural subtype whereas it bore no significant effect in proneural, mesenchymal, or classical GBM subtypes. Moreover, their study corroborated that oligonucleotide-based specific inhibition of TGF-β 3 significantly reduced invasiveness in vitro as well as in vivo [ 33 ].…”
Section: Discussionmentioning
confidence: 73%
“…Aberrant TGF-β signaling is considered as a hallmark of certain diseases. Three isoforms of TGF-β exist, including TGF-β1, TGF-β2 and TGF-β3, and targeting TGF-β3 represents a promising strategy interfering with aberrant TGF-β signaling in glioblastoma ( 58 ). TGF-β has also been implicated as an important mediator of renal fibrosis ( 59 ), and thus, the concentration of TGF-β was detected in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, isogenic GSCs "IT726R2" and "IT726R3"originating from different regions of ndGB #726 showed significant differences (p = 5.08 × 10 −12 ) in the number of cells required for generating clonal self-renewing spheres ( Figure 5A). Furthermore, there were also profound differences in the steady-state levels of several proteins implicated as therapeutic targets in GB such as glioma promoting factor TGFβ [41,42], TMZ-resistance factor MGMT [43], stemness marker CD133/Prominin-1 [44] or the marker of Proneural subtype PDFGRα [45] ( Figure 5). These results provide evidence that GSCs recapitulate interregional divergence at the cellular and molecular level.…”
Section: Recgb-derived Gscs Retain Transcriptomic Patterns Associatedmentioning
confidence: 99%